Molecular and morphological analyses revealed a cryptic species of dojo loach Misgurnus anguillicaudatus (Cypriniformes: Cobitidae) in Japan - R. Okada; T. Inui; Y. Iguchi; T. Kitagawa; K. Takata; T. Kitagawa (Journal of Fish Biology, 2017)
Although it has been reported that populations of the Japanese dojo loach Misgurnus anguillicaudatus (Cypriniformes: Cobitidae) belong to two distinct mitochondrial (mt)DNA (Type I and Type II), the taxonomic status of the species remains unresolved. To address this question, nuclear DNA and morphological analyses were performed on M. anguillicaudatus population in the Nakaikemi Wetland, where Type I and Type II lineages are sympatric. Results suggest the existence of a cryptic species (Type I) within the Japanese dojo loach.

Evaluation of the safety and efficacy of Glycyrrhiza uralensis root extracts produced using artificial hydroponic and artificial hydroponic-field hybrid cultivation systems - H. Akiyama; M. Nose; N. Ohtsuki; S. Hisaka; H. Takiguchi; A. Tada; N. Sugimoto; H. Fuchino; T. Inui; N. Kawano; S. Hayashi; A. Hishida; et al. (Journal of Natural Medicines, 2017)

Feeding habits of Hymenoptera and Isoptera in a tropical rain forest as revealed by nitrogen and carbon isotope ratios - F. Hyodo; Y. Takematsu; T. Matsumoto; Y. Inui; T. Itioka (Insectes Sociaux, 2011)

Inhibitor-associated transposition events in Corynebacterium glutamicum - T. R. Garbe; N. Suzuki; M. Inui; H. Yukawa (Molecular Genetics and Genomics, 2004)

Enhancement of metabolizing herbicides in young tubers of transgenic potato plants with the rat CYP1A1 gene - T. Yamada; T. Ishige; N. Shiota; H. Inui; H. Ohkawa; Y. Ohkawa (Theoretical and Applied Genetics, 2002)

Inducible cross-tolerance to herbicides in transgenic potato plants with the rat CYP1A1 gene - T. Yamada; Y. Ohashi; M. Ohshima; H. Inui; N. Shiota; H. Ohkawa; Y. Ohkawa (Theoretical and Applied Genetics, 2002)

Population pharmacokinetics of tacrolimus in adult recipients receiving living-donor liver transplantation - Fukatsu S.; Yano I.; Igarashi T.; Hashida T.; Takayanagi K.; Saito H.; Uemoto S.; Kiuchi T.; Tanaka K.; Inui K. (European Journal of Clinical Pharmacology, 2001)

NPC1 gene mutations in Japanese patients with Niemann-Pick disease type C - Toshiyuki Yamamoto; Eiji Nanba; Haruaki Ninomiya; Katsumi Higaki; Miyako Taniguchi; Haidi Zhang; Shinjiro Akaboshi; Yasuhiro Watanabe; Takao Takeshima; Koji Inui; Shintaro Okada; Akemi Tanaka; et al. (Human Genetics, 1999)

Cloning and expression of yellowtail ascites virus segment A - H. Sato; E. Emoto; T. Kamata; H. Mori; K. Kamei; A. Kitaoka; R. Takano; K. Nakajima; Y. Inui; K. Kudo; S. Hara (Archives of Virology, 1999)

Properties of human visual memory for block patterns - T. Inui (Biological Cybernetics, 1988)

The mechanism of mental scanning in foveal vision - T. Inui; M. Kawato; R. Suzuki (Biological Cybernetics, 1978)